2021
DOI: 10.1038/s41598-021-92612-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 epidemic on hospital admissions for alcohol-related liver disease and pancreatitis in Japan

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, there have been health concerns related to alcohol use and misuse. We aimed to examine the population-level change in cases of alcohol-related liver disease and pancreatitis that required admission during the COVID-19 epidemic by interrupted time series (ITS) analysis using claims data. We defined the period from April 2020, when the Japanese government declared a state of emergency, as the beginning of the COVID-19 epidemic. This ITS analysis included 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 16 publications
2
31
1
Order By: Relevance
“…Mortality associated with ALD increased across age, race, and sex during the US epidemic [70] , [71] . According to statistics from 257 hospitals in Japan during the epidemic, the admission rate per 1,000 people admitted for ALD or pancreatitis was 1.22 times that in the preepidemic period [72] . Meanwhile, the increase in the admission rate has increased the risk of patients being exposed to SARS-CoV-2.…”
Section: Chronic Liver Disease Complicated By Sars-cov-2 Infectionmentioning
confidence: 99%
“…Mortality associated with ALD increased across age, race, and sex during the US epidemic [70] , [71] . According to statistics from 257 hospitals in Japan during the epidemic, the admission rate per 1,000 people admitted for ALD or pancreatitis was 1.22 times that in the preepidemic period [72] . Meanwhile, the increase in the admission rate has increased the risk of patients being exposed to SARS-CoV-2.…”
Section: Chronic Liver Disease Complicated By Sars-cov-2 Infectionmentioning
confidence: 99%
“…Similar trends were also observed in other countries outside the US. For example, hospitalizations for alcohol-associated liver disease and alcohol-related pancreatitis in Japan increased by 20% during the pandemic [27] . Studies from Canada and England also reported a near doubling of hospital admissions for AH after the onset of the COVID-19 pandemic [28 , 29] .…”
Section: Impact On Epidemiology Of Alcohol-associated Liver Diseasementioning
confidence: 99%
“… Alcohol-Associated Liver Disease Burden Deutsch-Link et al. (2022) [27] ALD mortality Cross-sectional United States mortality data from the National Center for Health Statistics From 2019 to 2020, ALD-related mortality increased 21% in males and 27% in females. Highest relative increases observed in those under age 45.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of personal circumstances suggested that differences arose based on whether participants had children in the home; having children in the home was associated with an increase in alcohol consumption (also seen in Acuff et al, 2022 ). Investigations of the effects of the pandemic on alcohol consumption in Japan are focused on alcohol-use disorders and suggest that there has been an increase in admissions to hospital for alcohol-related illness due to the COVID-19 pandemic ( Itoshima et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%